INTRODUCTION OF THE SYSTEM OF ETHNOPEDAGOPIC MEANS IN THE EDUCATIONAL PROCESS OF PRIMARY SCHOOL (ON THE EXAMPLE OF ETHNOPEDAGOGY OF THE CRIMEA-TATAR PEOPLE) (Pedagogy of Higher and Secondary Education, 2011)
The article reveals how best to implement the system of means of ethnopedagogy Crimean Tatar people in the educational process of primary school.
Keywords: means of ethnopedagogy Crimean Tatar people; upbringing of junior pupils